What's wrong with subjective rights?. Issue 3 (3rd April 2019) - Biggar, Nigel
ABSTRACT: In the last twenty years a critique of the idea of a right as the property of an individual subject has been articulated by some influential Anglican theologians – Joan Lockwood O'Donovan, Oliver O'Donovan and John Milbank. Their objections are considerably based on an argument about intellectual history. Broadly pursuing an intellectual trajectory first set by Leo Strauss and C. B. Macpherson, these theologians think that the very concept of a 'subjective right' is tied, certainly historically but perhaps also logically, to modern, Hobbesian social contract theory, and therefore to radical individualism and moral subjectivism. Therefore, they think that to affirm individual subjective rights is to exclude a larger objective order of moral right, and to undermine the authority of the claim of social obligation. Against this critique, this article, first, argues that a morally realist conception of subjective rights prevailed before Hobbes, and continued to prevail long afterwards. Second, the article proceeds to refute Ernest Fortin's thesis that Hobbes came to dominate modern rights-talk through John Locke. Finally, it suggests that the contemporary detachment of the concept of subjective rights from a larger context of objective moral right has more plausible and more proximate roots in twentieth century philosophical and cultural developments.